RAPD analysis of the genetic diversity of two natural populations of Paphiopedilum villosum var. Annamense rolfe. in the Lam Vien plateau - Thắm, Đặng Thị; Duy, Nông Văn; Tiến, Trần Văn; Triệu, Lê Ngọc; Trung, Khuất Hữu; Chính, Vũ Tiến (Vietnam Journal of Biotechnology, 2016)
Paphiopedilum villosum var. annamense Rolfe. is the attractive pot plant characterize by its larger and beautiful flower. Wild population of that orchid are now considered to be rare in nature as a result of habitat destruction and commercial preference. Thus, it is very important that actions should be taken to conserve this orchid before it becomes extinct. The information of genetic variation at both population and species levels is a scientific basic for species conservation. In this research, two populations of Paphiopedilum villosum var. annamense Rolfe were collected in Lam Dong province, Vietnam for analysing of genetic variation. RAPD directive was used to examine genetic variability in 20 individuals of two populations. The results showed that 25 bands were recorded from 12 specific identification primers. The percentages of polymorphic loci at species and population levels in the research were not high (Pt = 74.07%; P1 = 67.90%; P2 = 62.35%). However, in the first population, a higher percentage of polimorphic loci was observed as in the second one. Significant heterozygosity at both population and species levels was also low (HE1 = 0.23; HE2 = 0.18; and HEt = 0.25). The total gene diversity at the species level was partitioned primarily between two populations, as show by low GST= 0.17. Genetic distance between two populations was low (D12 = 0.079). In the orther hand, Genetic similarity coefficients between individuals in the general population were ranged from 0.57 to 0.91. The results suggested that the small population sizes in isolation had led to increase of inbred individuals within populations. Some solutions to the conservation and sustainable development have been mentioned.